Arthur Efron, Don Quixote and the dulcineated world. University of Texas Press, Austin, 1971; viii + 203 pp. - Rodríguez-Luis, Julio (El Colegio de México, 1973)
Se reseñó el libro: Don Quixote and the dulcineated world.